Human-AI Collaboration in Knowledge Management and Its Role in Enhancing Institutional Performance - Khalid Ali Alzahrani; Ibrahiem M. M. El Emary (Bright Institute, 2026)
This study reviews the literature on knowledge management (KM) and its role in improving institutional performance, with a focus on applications in institutional communication centers. It aims to assess the development of research in this field, identify key themes related to KM practices, and examine their impact on organizational performance, while outlining potential directions for future research. The study adopts an inductive analytical approach through the examination of relevant scientific publications to identify major trends and patterns in the literature. The review is contextualized within the Institutional Communication Center at King Abdulaziz University, Jeddah, during the academic year 1447 AH / 2025 AD, as a case reflecting the relationship between KM and institutional communication. The findings indicate that the effective implementation of KM practices contributes to improving institutional performance by enhancing service quality, supporting informed decision-making, and strengthening communication processes within the organization. In addition, integrating KM into communication environments supports the role of communication centers as key channels linking institutions with their stakeholders. The analysis also shows that digital transformation, particularly through social media and digital platforms, plays an important role in facilitating knowledge sharing, interaction, and innovation. Previous studies emphasize the importance of developing integrated KM strategies, enhancing employee capabilities, and promoting organizational flexibility to support sustained institutional performance. Overall, the study confirms that knowledge management represents an important approach for improving institutional performance, especially when aligned with communication functions and digital developments within organizations.